The Effectiveness of Collaborative Writing Strategy (CWS) In Improving EFL Learners’ Recount Text - Fitria Tokan; Satria Agust; Benni Satria (Juliet, 2023)
This study aims to determine whether Collaborative Writing Strategy (CWS) is more effective for students writing recount texts in the eighth grade at SMP Negeri 1 Bintan. The research design used in this study was quasi-experimental. The population for this study was eighth-grade students. In this population, two classes were chosen the experimental group (VIII-A) and the control group (VIII-B), each consisting of 29 students. The data for this study was taken from the pre-test and post-test scores of both groups. The data or writing scores of the students were analyzed in terms of frequency distribution, normality, homogeneity, and the T-test. Based on the result of the analysis, there were different means in the experimental group 74.35 in the post-test. The control group was 67.67 in the post-test. The t-test formula was used. Based on the result of the computation, the t-value is 2.133. Based on the result of interpolation, the critical value is 1.701. The t-value is higher than the t-table (2.133 > 1.701). It means that using the Collaborative Writing Strategy (CWS) to teach and learn to write recount texts is more effective.